PENGARUH PERSEPSI HARGA DAN FASILITAS TEMPAT WISATA TERHADAP MINAT BERKUNJUNG ULANG KONSUMEN DI CAFFE BANG NDUT The Effect of Price Perception and Tourist Facility on Consumer Revisit Intention at Caffe Bang Ndut - Siti Nur Holilah; Sri Redjeki; Pudhak Prasetiyorini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of price perception and tourist facility on consumer revisit intention at Caffe Bang Ndut, Jember Regency. A quantitative approach with causal-associative design was employed. Data were collected through questionnaires distributed to 30 respondents who were consumers of Caffe Bang Ndut, using incidental sampling. The instrument was measured using a Likert scale and tested for validity and reliability. Data analysis involved multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that: (1) price perception positively and significantly affects revisit intention (sig. 0.012 < 0.05); (2) tourist facility positively and significantly affects revisit intention (sig. 0.004 < 0.05); and (3) price perception and tourist facility simultaneously have a significant effect on revisit intention (F = 18.742; sig. 0.000 < 0.05). The coefficient of determination (R²) is 0.581, meaning the two variables explain 58.1% of the variance in consumer revisit intention. These findings have practical implications for Caffe Bang Ndut management in designing more effective pricing and facility management strategies to enhance consumer loyalty.